Self-assembled thin polymer film used for sensing application - Li, Feng (Kansas State University, 2013)
Polymer thin films have played an important role in our everyday lives ranging from industrial to biomedical applications. In this thesis, two major topics based on polymer thin films including photopolymerized self-assembled monolayer and nanoporous thin films derived from diblock copolymer are discussed. In the first part of this thesis, a well-packed self-assembled monolayer with phosphonic acid as head group and diacetylenic functional group in the tail formed on AlGaN/GaN surface. According to water contact angle and UV/Vis absorption spectroscopy data, the stability of this self assembled monolayer on oxidized AlGaN/ GaN surface can be improved by photopolymerization of SAMs. The photopolymerization efficiency of the SAMs is effected by the position of polymerization functional group in the alkyl chain. In the second part of this thesis, PS-b-PMMA diblock copolymer thin films were prepared, characterized and applied as a template for electron transfer efficiency determination. The surface COOH group in nanoporous thin films derived from PS-b-PMMA were modified with ferrocene redox moieties having different linker lengths in the organic phase. The surface functionalization efficiency was quantitatively assessed by measuring the monovalent probe cations released from the surface COOH groups via cation-exchange processes using highly- sensitive analytical techniques including spectrofluorometry and inductively coupled plasma mass spectrometry (ICP-MS). The surface coverage of the redox moieties is an important parameter to determine the electron hopping efficiency. The electron propagation resulted from electron hopping across relatively large spacing that was controlled by the motion of anchored redox sites. The longer linker led to the larger physical displacement range of anchored ferrocene moieties, facilitating the approach of the adjacent ferrocene moieties within a distance required for electron self-exchange reaction. Faradic currents originating from redox-involved electron hopping through the ferrocene moieties anchored onto the insulator surface decreased with increasing the concentration of beta-cyclodextrin ([beta]-CD) in aqueous solution. The current could be recovered by adding redox-inactive guest molecules of [beta]-CD to the solution.
Keywords: Surface chemistry; Block copolymer; Electrochemistry; Chemistry (0485)